(untitled) (Scientific journal of the Fergana State University, 2026)
In this article, the activities of the people’s education system of the Namangan region during the Second World War, the courses to eliminate illiteracy, the training of military personnel, the attendance of school students, the positive and negative aspects of the educational system are discussed.